Humic Acid Enhances Antioxidant and Glyoxalase Systems to Combat Copper Toxicity in Citrus - Wei-Tao Huang; Xu-Feng Chen; Wei-Lin Huang; Qian Shen; Fei Lu; Ning-Wei Lai; Jiuxin Guo; Lin-Tong Yang; Xin Ye; Li-Song Chen (Agronomy)
Most commercial citrus fruits are grown in acidic soils with high copper (Cu) and low organic matter levels in China. Sweet orange (Citrus sinensis (L.) Osbeck cv. Xuegan) seedlings were treated with 0 (HA0), 0.1 (HA0.1), or 0.5 (HA0.5) mM humic acid (HA) and 0.5 (Cu0.5) or 400 (Cu400 or Cu excess) μM CuCl2 for 24 weeks. The purpose was to validate the hypothesis that HA reduces the oxidative injury caused by Cu400 in roots and leaves via the coordination of strengthened antioxidant defense and glyoxalase systems. Copper excess increased the superoxide anion production rate by 27.0% and 14.2% in leaves and by 47.9% and 33.9% in roots, the malonaldehyde concentration by 199.6% and 27.8% in leaves and by 369.4% and 77.4% in roots, and the methylglyoxal concentration by 18.2% and 6.6% in leaves and by 381.8% and 153.3% in roots, as well as the H2O2 production rate (HPR) by 70.5% and 16.5% in roots, respectively, at HA0 and HA0.5. Also, Cu400 increased the leaf HPR at HA0, but not at HA0.5. The addition of HA reduced the Cu400-induced production and accumulation of reactive oxygen species and methylglyoxal and alleviated the impairment of Cu400 to the antioxidant defense system (ascorbate-glutathione cycle, antioxidant enzymes, sulfur-containing compounds, and sulfur-metabolizing enzymes) and glyoxalase system in roots and leaves. The HA-mediated amelioration of Cu toxicity involved reduced oxidative injury due to the coordination of strengthened antioxidant defense and glyoxalase systems. These findings highlight the promise of HA for sustainable citrus cultivation in heavy metal (Cu)-polluted soils.